Simple and Rapid LC-MS/MS Method for Determination of Perampanel in Human Plasma and Application to Bioequivalence Study - Gao, Pan; Zou, Qiao-gen (Current Pharmaceutical Analysis, 2022)
Background: Perampanel (PER) is a third-generation antiepileptic drug (AED). Several methods have been developed for the quantification of perampanel in plasma. The pharmacokinetic characteristics of perampanel in healthy Chinese ubjects have not been comprehensively reported. Objective: A simple, fast and sensitive LC-MS/MS method was established and validated for the quantification of perampanel in human plasma and its application to a bioequivalence study. Methods: Chromatographic separation was accomplished on a ZORBAX Eclipse XDB-Phenyl column (4.6 mm × 75 mm, 3.5 μm) using a binary gradient with mobile phase (A) (water containing 5 mmol/L ammonium acetate and 0.1% formic acid and (B) acetonitrile-water (95:5, v/v) at a flow rate of 0.9 mL/min and sample preparation was by one-step protein precipitation via acetonitrile. Results: The total run time in this study was 4.5 min and the retention time of perampanel and perampanel-d5 (internal standard) were 2.30 min and 2.32 min, respectively. The method was developed and validated over the concentration range of 2.00-500 ng/mL for perampanel, with a correlation coefficient greater than 0.9992. The inter-day precision was 3.1%-3.8% and accuracy was 98.9%-103.5%. The intra-day precision was 2.4%-6.8% and the accuracy was 97.6%- 104.9%. The extraction recovery ranged from 99.23%-103.84% and the matrix effect was not significant. Perampanel was proved to be stable in solution and human plasma under different tested conditions. The validated method was successfully applied to a randomized, open-label, 2- period, crossover bioequivalence study in healthy Chinese subjects, and the results indicated that bioequivalence was achieved for 2 formulations of the 4-mg perampanel tablet under both fasting and fed conditions, and both treatments were safe and well-tolerated by all study subjects. Conclusion: The validated method was successfully applied to a bioequivalence study of perampanel in human plasma and has achieved satisfactory results.
Keywords: bioequivalence study